Evidence That Management Discussion and Analysis (MD&A) is a Part of a Firm's Overall Disclosure Package* - CLARKSON, PETER M.; KAO, JENNIFER L.; RICHARDSON, GORDON D. (Contemporary Accounting Research, 1999)
Abstract The objective of this study is to investigate the role, if any, that management discussion and analysis (MD&A) plays in a firm's disclosure package. First, we present evidence regarding the usefulness of MD&A. Our evidence is uniformly supportive of the view that MD&A is a source of new and useful information and indicates that MD&A is used for financial analysis purposes by at least one significant user group, sell‐side analysts, who are members of the Toronto Society of Financial Analysts. We then provide evidence on disclosure quality. The results reveal that, overall, MD&A disclosure quality varies with disclosure stimuli similar to those found to influence disclosure choice in other disclosure channels. However, a more refined analysis of the MD&A subcomponents reveals that different factors influence disclosure quality for those subcomponents. Taken together, our results are consistent with the notion that MD&A is a part of a firm's overall disclosure package.